2002
DOI: 10.1046/j.1432-1033.2002.03199.x
|View full text |Cite
|
Sign up to set email alerts
|

The β‐1,4‐endogalactanase A gene from Aspergillus niger is specifically induced on arabinose and galacturonic acid and plays an important role in the degradation of pectic hairy regions

Abstract: The Aspergillus niger b-1,4-endogalactanase encoding gene (galA) was cloned and characterized. The expression of galA in A. niger was only detected in the presence of sugar beet pectin, D-galacturonic acid and L-arabinose, suggesting that galA is coregulated with both the pectinolytic genes as well as the arabinanolytic genes. The corresponding enzyme, endogalactanase A (GALA), contains both active site residues identified previously for the Pseudomonas fluorescens b-1,4-endogalactanase.The galA gene was overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…Several fermentation studies showed that B. longum was able to use polymeric arabinogalactan as a substrate (9,11,42). This paper provides the first description of a polysaccharide-degrading enzyme from B. longum, further supporting the view that galactans can be fermented by bifidobacteria.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Several fermentation studies showed that B. longum was able to use polymeric arabinogalactan as a substrate (9,11,42). This paper provides the first description of a polysaccharide-degrading enzyme from B. longum, further supporting the view that galactans can be fermented by bifidobacteria.…”
Section: Discussionsupporting
confidence: 64%
“…Since the genome sequence of Bifidobacterium longum recently became available (36), more information about Bifidobacterium glycolytic enzymes has been uncovered. The genome reveals that approximately 5% of all annotated genes are involved in the modification of carbohydrates.Several studies on in vitro fermentations of (␤13 4)-linked (arabino)galactans with different bifidobacteria show that mainly B. longum strains were able to grow on these arabinogalactans (9,11). This is consistent with the genome sequence of B. longum because it reveals the presence of many different putative enzymes potentially able to degrade arabinogalactans.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…20% of the pectin oligosaccharides (45). Type I galactan is degraded by 1,4-␤-endogalactanases and 1,4-␤-exogalactanases (12). Galactanases are widely distributed into many plants.…”
mentioning
confidence: 99%
“…They cause the solubilization of pectin oligosaccharides and seem to play a major role in ripening of fruits (29,32). 1,4-␤-Endogalactanase has been also isolated from microorganisms, including aerobic fungi belonging to the genus Aspergillus (12) and bacteria such as Bacillus subtilis (13), Pseudomonas fluorescens (9), and Thermotoga maritima (44).…”
mentioning
confidence: 99%